Estimação de uma função de custos em processo de terceirização em empresa de serviços - Silva, Leandra da (2019)
Submitted by JOSIANE SANTOS DE OLIVEIRA (josianeso) on 2019-08-27T14:20:34Z No. of bitstreams: 1 Leandra da Silva_.pdf: 761047 bytes, checksum: 83f2f721eaf910c41abcf69ad17385de (MD5)